DIMENSI FRAUD HEXAGON TERHADAP ACADEMIC FRAUD PADA MAHASISWA PROGRAM STUDI AKUNTANSI UNIVERSITAS BALIKPAPAN - Amanda Polapa, Rizaldi; Azizil Yudharuddin, Yanzil; Karlinda Sari, Dika (Fakultas Ekonomi Universitas Balikpapan, 2025)
This study aims to examine the effect of Pressure, Opportunity, Rationalization, and Ability on Academic Fraud in Accounting Study Program Students at Balikpapan University. The type of research used is quantitative research. The sampling technique uses a purposive sampling method which produces 130 student respondents samples from a population of 202 Stundents respondents. The data analysis method used was Outer model, Inner Model, and Hypothesis Testis. The results of this study indicate that Pressure, Rationalization, ability and collusion have an effect on academic cheating. While the results of the study show that opportunity and arrogance do not have an effect on academic cheating.